2002
DOI: 10.30843/nzpp.2002.55.3933
|View full text |Cite
|
Sign up to set email alerts
|

Temperaturedependent development of parasitoids on two species of armoured scale insects

Abstract: The duration of development of the parasitoid Encarsia citrina (Craw) (Hymenoptera Aphelinidae) on its hosts greedy scale Hemiberlesia rapax (Comstock) and oleander scale Aspidiotus nerii Bouché (Hemiptera Diaspididae) and of Signiphora merceti (Malenotti) (Hymenoptera Signiphoridae) on greedy scale was determined at five constant temperatures Weibull functions were fitted to the cumulative distribution of parasitoid emergence times and development rates for 5 50 and 95 emergence were calculated Development ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…), and several biological control studies have demonstrated this for hymenopteran parasitoids (Ables et al . ; Minkenberg ; Logan & Thomson ). In addition, some parasitoids that enter diapause at low temperatures are triggered by higher temperatures to break diapause and continue development (Hertlein ; Garcia et al .…”
Section: Discussionmentioning
confidence: 99%
“…), and several biological control studies have demonstrated this for hymenopteran parasitoids (Ables et al . ; Minkenberg ; Logan & Thomson ). In addition, some parasitoids that enter diapause at low temperatures are triggered by higher temperatures to break diapause and continue development (Hertlein ; Garcia et al .…”
Section: Discussionmentioning
confidence: 99%
“…Matadha et al (2004) evidenced that 15 and 30° C appear to be lower and upper temperature thresholds for E. citrina oviposition and larval development on San Jose scale, Q. perniciosus. Contrarily, Logan and Thompson (2002) observed extended development times of ≈75 and 125 d, with 95 % emergence of E. citrina at 15° C on both greedy and oleander scales, respectively. Accordingly, the effect of these extreme temperatures on the estimated biological parameters did not examine.…”
Section: Discussionmentioning
confidence: 86%
“…The second hypothesis, that host population would affect the thermal phenotype of the parasitoid, was not supported by the results obtained, although such effects have been reported from other Trissolcus spp.-host combinations (e.g., Nozad Bonab & Iranipour, 2012). It is also true in other parasitoid-host systems (Logan & Thomson, 2002;Li & Mills, 2004).…”
Section: Discussionmentioning
confidence: 92%